The efficiency of the portuguese agricultural credit co-operatives governance model - Cabo, Paula (2014)
In recent years the importance of corporate governance (CG) has rising new attention, as the 2008 financial crisis illustrates. Co-operative members, staff, regulators and others stakeholders involved in the co-operative banking business became aware of the need to strengthen co-operatives governance, since this is crucial to safeguarding sound management and, ultimately, to the survival and sustainability of these organizations. With their origins rooted in the 16th century, the Portuguese Agricultural Credit Co-operatives (CCAM) have been considered central players in the economic and social development of rural regions. The goal of this paper is to determine the impact of the different governance mechanisms of co-operative banks on control management, by analysing CCAM governance and assess its efficiency in disciplining management. Hence, using data from 1995-2009 period, and multinomial logit models, the relation between CCAM performance and several control mechanisms operating within the SICAM is analysed. The results show that overall internal governance mechanisms are not related to the CCAM performance, which indicates potential weakness of the CCAM internal control mechanisms. On the other hand, external governance mechanisms are related to CCAM operational and cost efficiency indicators, demonstrating the importance of these mechanisms in disciplining CCAM management. Moreover, the results highlight the value of the supervision task of Central CCAM in the performance of the associates.